Conventional soliton and noise-like pulse emissions at 1.98μ m utilizing tungsten trioxide as mode-locker - Yusoff, Norita Mohd; Ahmed, Mahmoud Hazzaa Mohamed; Ng, Eng Khoon; Abidin, Nadiah Husseini Zainol; Alresheedi, Mohammed Thamer; Mahdi, Mohd Adzir (World Scientific, 2025)
In this paper, we experimentally demonstrate the dual pulse emissions of conventional soliton (CS) and noise-like pulse (NLP) in thulium-holmium co-doped fiber laser using tungsten trioxide saturable absorber (WO3-SA). The CS pulse delivered 2ps width, centered at 1982.8nm. Increasing the pump power and alteration of polarization states switched the CS to the NLP regime with 1990.0nm central wavelength, 17.2nm spectral bandwidth, and 396fs spike width riding on top of a wide picosecond pulse pedestal in the time domain. This work suggests the capability of WO3-SA as a pulse initiator for future dual-source ultrashort pulses based on an all-fiber laser cavity design.